2013
DOI: 10.1111/1365-2664.12173
|View full text |Cite
|
Sign up to set email alerts
|

Modelling edge effects of mature forest plantations on peatland waders informs landscape‐scale conservation

Abstract: Summary1. Edge effects of native forest fragmentation have been well studied, but there are few studies of open-ground habitats fragmented by plantation forests. We measure forestry edge effects on open-ground breeding birds, following one of Europe's biggest and most controversial land-use transformations. 2. The 'Flow Country' of northern Scotland is one of the world's greatest expanses of blanket bog. It became fragmented by conifer forests planted in the late 20th century, and these now adjoin open peatlan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 57 publications
5
58
0
Order By: Relevance
“…Pearce-Higgins and Grant [97] and Wilson et al [98] showed that the rate of predation on wader nests greatly increases when bushes, shrubs and trees are present on or near habitat patches, thus providing perches for predators. In contrast, a study by Ottvall et al [99] indicates that wader nest survival rates were not related to the distance to habitat edges or other features used by predators.…”
Section: Birds Of Preymentioning
confidence: 99%
“…Pearce-Higgins and Grant [97] and Wilson et al [98] showed that the rate of predation on wader nests greatly increases when bushes, shrubs and trees are present on or near habitat patches, thus providing perches for predators. In contrast, a study by Ottvall et al [99] indicates that wader nest survival rates were not related to the distance to habitat edges or other features used by predators.…”
Section: Birds Of Preymentioning
confidence: 99%
“…; Wilson et al . ). The response of forest biodiversity to the afforestation of agricultural land, however, is complex (Felton et al .…”
Section: Introductionmentioning
confidence: 97%
“…Golden Plovers breed in open habitats and show avoidance of tall objects in these landscapes, such as plantation forestry, which can reduce breeding abundance within about 700 m of forest edges (Wilson et al . ). It is highly likely that a similar mechanism of avoidance of tall structures in a previously open landscape was operating in the present study.…”
Section: Discussionmentioning
confidence: 97%